Efficacy of antioxidant mouthwash in the reduction of halitosis: A randomized, double blind, controlled crossover clinical trial - Alsaffar, Duaa (J Dent Sci, 2021)
BACKGROUND/PURPOSE: Halitosis is the unpleasant and offensive odour in exhaled air, which is linked to the presence of volatile sulphur compounds (VSC). Different mouthwashes have been used to treat halitosis. The objective of this study was to test the effect of an antioxidant (AO) mouthwash, and mouthwash containing [0.05% chlorhexidine, 0.05% cetylpyridinium chloride, and 0.14% zinc lactate (CHX-CPC-Zn)] on VSC. MATERIAL AND METHODS: Thirty-five subjects with halitosis participated in this clinical trial. At the baseline visit, a breath sample was taken and analyzed for the level of hydrogen sulphide (H(2)S), methyl mercaptan (CH(3)SH), and dimethyl sulphide (CH(3)SCH(3)) using portable gas chromatography (OralChroma™). Two mouthwashes were randomly provided to each subject in addition to saline solution (NaCl 0.9%) as control. Subjects were instructed to rinse with 20 ml of the mouthwash for 1 min twice daily for 2 weeks. At second visit, post-treatment breath sample was taken. Afterward, the patient was asked to refrain from using mouthwash for a washout period of 1 week. A similar procedure was repeated for each mouthwash interval. RESULTS: No significant differences in VSC level between all three groups were detected at baseline. A significant reduction in VSC level was obtained after using CHX-CPC-Zn mouthwash. On other hand, both AO mouthwash and saline had no significant impact on the level of VSC. CONCLUSION: CHX-CPC-Zn mouthwash has a significant effect on VSC level reduction in subjects with confirmed halitosis. Besides, using AO mouthwash regularly for 2 weeks did not have any impact on improving the level of halitosis.